Toplogical Data Analysis Detects and Classifies Sunspots (Student Abstract) - Lytle, Aidan; Pritchard, Neil; Aarnio, Alicia; Weighill, Thomas (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
In our technology-dependent modern world, it is imperative to monitor the Sun for space weather threats to critical infrastructure. Topological data analysis (TDA) is a new set of mathematical techniques used in data analysis and machine learning. We demonstrate that TDA can robustly detect and classify solar surface and coronal activity. This technique is a promising step toward future application in predictive space weather modeling.